Down the Bright Stream the prehistory of Woodcock Corner and the Tregurra Valley, Cornwall - Taylor, Sean R. (Archaeopress Publishing, 2022)
Down the Bright Stream: The Prehistory of Woodcock Corner and the Tregurra Valley reports on a series of fieldwork projects carried out in the Tregurra Valley, to the east of Truro, Cornwall. The work was undertaken over a period of seven years between 2009 and 2015, predominantly by the Cornwall Archaeological Unit, as a response to the development of the valley. The fieldwork led to the identification of a large number of pits and hearths across the site, the majority of which that have proved dateable spanning the Early Neolithic to the end of the Early Bronze Age. One concentration of pits included one dating to the Late Neolithic containing a remarkable engraved slate disc. Other pits contained evidence for tin processing at the start of the Bronze Age. An enclosure formed by a segmented ditch was dated to the Early Bronze Age. Of considerable note was the identification of buried soils and colluvial layers pre-dating much of the prehistoric activity and found across the site. There was an apparent absence of activity in the valley between the end of the Early Bronze Age and the start of the Iron Age, when much of the valley was enclosed with field boundary ditches and activities recorded include crop processing, charcoal burning and iron smelting. The charcoal burning continued into the medieval period. Later activity in the valley including brickmaking, stone quarrying, and small-scale mineral prospection, is reported on elsewhere
Keywords: Vor- und Frühgeschichte; Glockenbecherkultur; Archäologie; Ausgrabung; Siedlungsarchäologie; Neolithikum; Eisenzeit; Bronzezeit; Funde; Großbritannien; Cornwall; Woodcock corner; Tregurra Valley (England) / History / To 1500; Cornwall (England : County) / Antiquities